Delivera flow / Sajad Saggaf - Saggaf, Sajad (Faculty of Computer and Mathematical Sciences, 2023)
Delivera Flow project aims to address the challenges faced by the logistics industry in accurately tracking the locations of packages during transportation. As the global supply chain grows more complex, ensuring the security and timely delivery of packages has become a critical concern for businesses and customers alike. This project seeks to leverage advanced sensor technologies to create a comprehensive solution that enhances package tracking, security, and overall efficiency.